Coronarin K and L: Two Novel Labdane Diterpenes From Roscoea purpurea: An Ayurvedic Crude Drug - Singamaneni, Venugopal; Lone, Bashir; Singh, Jasvinder; Kumar, Pankaj; Gairola, Sumeet; Singh, Shashank; Gupta, Prasoon (Frontiers in Chemistry, 2021)
The main objective of cancer treatment with chemotherapy is to kill the cancerous cells without affecting healthy normal cells. In the present study, bioactivity-guided purification of n-chloroform soluble fraction from the methanol extract of Roscoea purpurea resulted in the isolation of two new labdane diterpenes, coronarin K (1) and coronarin L, (2) along with eight known compounds, coronarin A (3), bisdemethoxycurcumin (4), kaempferol 3-O-methyl ether (5), kaempferol (6), fenozan acid (7) 3-(3-methoxy,4-hydroxyphenyl)-2-propenoic acid (ferulic acid, 8), caffeic acid (9) and gallic acid (10). The structures of new compounds (1–2) were determined by detailed analysis of 1D and 2D NMR spectroscopic data and the relative configurations were determined with the help of NOESY data and comparison of optical rotations with similar compounds with established stereochemistry, while known compounds were confirmed by direct comparison of their NMR data with those reported in literature. This is the first report of isolation of this labdane diterpenes and phenolic classes of secondary metabolites in Roscoea purpurea. In the preliminary screening the methanol extract and its fractions were tested for the cytotoxic activity against a panel of four cancer cell lines (A549, HCT-116, Bxpc-3 and MCF-7), extract and its chloroform fraction were found to be active against lung cancer cell line, A-549 with IC50 value of <25 μg/mL. Owing to the notable cytotoxic activity of the chloroform fraction, the isolated compounds (1-5) were evaluated for their cytototoxicity against all the cell lines by MTT assay. Coronarin K, 1 showed significant cytotoxic potential against lung cancer cell lines (A-549), with IC50 value of 13.49 μM, while other compounds did not show activity below 22 μM.